2015
DOI: 10.1016/j.jped.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizures: a population-based study

Abstract: The prevalence of febrile seizures in Midwestern Brazil was lower than that found in other Brazilian regions, probably due to the inclusion only of febrile seizures with motor manifestations and differences in socioeconomic factors among the evaluated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…The protective effect of a high income level in the per-person analysis was an interesting finding. The study of Verity et al [15] showed no significant difference in the prevalence of febrile seizures with the educational level or socioeconomic status of the parents in the British national cohort; however, Dalbem et al [6] reported a lower incidence of febrile seizures in higher socioeconomic regions in Brazil. Dalbem et al [6] assumed that the higher socioeconomic regions had better sanitation facilities and thus would have less febrile illness and a lower incidence of febrile seizures.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The protective effect of a high income level in the per-person analysis was an interesting finding. The study of Verity et al [15] showed no significant difference in the prevalence of febrile seizures with the educational level or socioeconomic status of the parents in the British national cohort; however, Dalbem et al [6] reported a lower incidence of febrile seizures in higher socioeconomic regions in Brazil. Dalbem et al [6] assumed that the higher socioeconomic regions had better sanitation facilities and thus would have less febrile illness and a lower incidence of febrile seizures.…”
Section: Discussionmentioning
confidence: 94%
“…The study of Verity et al [15] showed no significant difference in the prevalence of febrile seizures with the educational level or socioeconomic status of the parents in the British national cohort; however, Dalbem et al [6] reported a lower incidence of febrile seizures in higher socioeconomic regions in Brazil. Dalbem et al [6] assumed that the higher socioeconomic regions had better sanitation facilities and thus would have less febrile illness and a lower incidence of febrile seizures. We consider that the lack of proper sanitation and the possibility of higher parental anxiety and family dysfunction could be the reasons for the higher incidence of febrile seizures in the lowincome families in this study [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only one study in Brazil has observed the same rate; however, the authors have evaluated only patients ≥ 15 years old ( 22 ). Another Brazilian study has observed an average age of the first childhood febrile seizure of 1.6 ( 26 ) in children aged 0–5 years. Shrestha et al ( 27 ) have analyzed the clinical characteristics of children with febrile seizures in a hospital in Nepal and found that most children (72.8%) presented their first episode of seizure below 24 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…This association is not surprising, considering that febrile seizure is classified as the most prevalent seizure type in the pediatric population. However, these seizures generally do not represent long-term neurological complications associated with epileptic diseases [31].…”
Section: Causes Of Seizure In Childrenmentioning
confidence: 99%